Factors associated with quality of life of breast cancer patients who have completed treatment at Oncology clinic, Teaching Hospital Jaffna - Vishnuveni, K.; Puvithira, T.; Jegapragash, V.; Thanenthiran, A.J. (University of Jaffna, 2023)
Introduction: The most prevalent malignancy diagnosed in women is breast cancer. Improvements in diagnosis and treatment have significantly increased breast cancer survival rates. Despite the improvements, it has negative impacts on the Quality of life (QOL) of patients. Identifying the factors associated with QOL may offer insights into how to manage and care for patients with breast cancer. Objective: To assess the QOL and its associated factors in breast cancer patients who have completed treatment at the Oncology clinic, Teaching Hospital Jaffna. Methodology: A hospital-based descriptive cross-sectional study was conducted among 114 breast cancer patients who have completed 6-month surveillance from initial treatment at the Oncology clinic, Teaching Hospital Jaffna. An interviewer-administered questionnaire was used to collect the data. The WHOQOL-BREF was used to assess the QOL of the participants. The data were analyzed by using IBM SPSS version 27. The variables were described by descriptive statistics and Whitney and Kruskal statistical test was used to find the associated factors. The ethical clearance was obtained from the Ethics Review Committee of the Faculty of Medicine, University of Jaffna. Results: The mean age of the participants was 57 years (SD=11.876) and all the participants were female. The overall QOL of the participants was 55.98 ±SD 14.107. The median scores of Physical, Psychological, Social and Environmental domains were 56.0 (43.3- 69.0), 56.0 (44.0- 69.0), 51.0 (44.0- 69.0) and 56.0 (50.0- 69.0) respectively. 30-59 aged group patients had higher physical, psychological and environmental QOL. Unmarried women had better social QOL. The patients with good family support had higher QOL in all domains. The overall QOL was significantly associated with the level of education, occupation, monthly income, family support, comorbidities, and chemotherapy. Conclusion: The overall QOL (55.98 ± 14.10 out of 100) and the QOL domains were average in this study.
Keywords: Quality of life; Breast cancer; WHOQOL-BREF; Domain